La protesta en tiempos extraordinarios: un análisis de su dinámica segmentada durante la cuarentena (Argentina, 2020) (2022)
From the quarantine imposed by the National Government in response to the SARS-CoV-2 pandemic, many economic and social activities were affected. Social protest was no exception, as various actors encountered new and old demands, which, in this context, became even more urgent. Faced with this situation, we ask ourselves: What characteristics did the protest take on during the quarantine? Who demonstrated? What were their demands and repertoires of action? Based on the method of analysis of counting protest events, this article reconstructs the dynamics of social protest during quarantine by identifying its main organizations, demands, formats, and places where it took place. The period analyzed was from March 16 to June 7, 2020. The analysis was conducted from the survey of information in four printed and digital journalistic sources. The hypothesis that organizes the article argues that during this period the use of segmented protests with a tendency to denationalized localization and specific demands prevailed. Thus, this type of protest was constituted as one of the strategies of the organizations, which were complemented by institutional negotiations.